2021
DOI: 10.1177/21582440211050389
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits, STEM, and Medicine: Autism Spectrum Quotient Scores Predict Medical Students’ Career Specialty Preferences

Abstract: There is a higher than chance representation of autistic people and people with elevated autistic traits in Science, Technology, Engineering and Mathematics (STEM) industries. Medical students, despite studying a STEM subject, have lower autistic traits than other STEM students. Medicine is heterogenous, covering technique-oriented specialties (e.g., surgery) with little patient interaction, person-oriented specialties (e.g., pediatrics), and general practice. We present an online survey in which 502 UK univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
2
1
Order By: Relevance
“…Unlike other studies, which indicate strong representation on STEM programmes in the United States (Anderson et al, 2017;Shattuck et al, 2014;Wei, et al, 2014) and the Netherlands (Bakker et al, 2019), our UK findings reported low levels of those who graduated from other STEM subjects such as Engineering and Technology, Medicine, Dentistry, Allied Medicine, or Veterinary Science although proportionately high levels of participation in Computer Science. The small numbers studying medicine echo the findings from the study by Turner et al (2021) who find that medical students in the United Kingdom have significantly lower levels of autistic traits compared to other STEM students and non-STEM students and might, therefore, be less drawn to person-oriented academic programmes or careers. While this could be the case, differential rates could also be due to under-reporting, where autistic graduates in these particular fields did not participate in the data collection.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Unlike other studies, which indicate strong representation on STEM programmes in the United States (Anderson et al, 2017;Shattuck et al, 2014;Wei, et al, 2014) and the Netherlands (Bakker et al, 2019), our UK findings reported low levels of those who graduated from other STEM subjects such as Engineering and Technology, Medicine, Dentistry, Allied Medicine, or Veterinary Science although proportionately high levels of participation in Computer Science. The small numbers studying medicine echo the findings from the study by Turner et al (2021) who find that medical students in the United Kingdom have significantly lower levels of autistic traits compared to other STEM students and non-STEM students and might, therefore, be less drawn to person-oriented academic programmes or careers. While this could be the case, differential rates could also be due to under-reporting, where autistic graduates in these particular fields did not participate in the data collection.…”
Section: Discussionsupporting
confidence: 62%
“…They also found that female autistic students tended to opt for jobs, which helped others compared to their male autistic peers. This runs counter to the claim by Turner et al (2021) that autistic students might be less likely to pursue personfocused career paths and could indicate that education offers a professional environment where autistic graduates feel able to utilise knowledge and skills acquired at university. In fact, StEvens (2022, p. 2) suggests that their 'autistic experience gives an advantage in implementing inclusive education practices'.…”
Section: Discussioncontrasting
confidence: 59%
“…With excellent attention to detail, and the ability to remain focussed on pattern-based tasks, autistic people are more likely to work in Science, Technology, Engineering, and Mathematics (STEM) 12,[51][52][53][54] . This effect extends to people who display higher than average levels of autistic traits but do not have a clinical diagnosis 12,[55][56][57][58][59] . Empathizing and systemizing may therefore be important variables to consider within the assortative mating paradigm.…”
mentioning
confidence: 89%
“…Scholars have taken a slow but emerging interest in the presence of autistic traits among certain professional groups. Several studies lend credence to the intuition that ‘high-functioning’ people with an autistic condition often gravitate toward the STEM professions (Baron-Cohen et al, 2001 , 2007 ; Turner et al, 2021 ). In particular, recent attention has been given to links between autistic traits and psychological distress such as depression and burnout among Japanese medical students and pharmacists (Higuchi et al, 2015 , 2016 , 2017 ; Watanabe et al, 2021 ; Watanabe & Akechi, 2023 ).…”
Section: Introductionmentioning
confidence: 89%